2016
DOI: 10.1538/expanim.16-0011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of phenylhydrazine induced hyperbilirubinemia in experimental rabbit

Abstract: Induction of hyperbilirubinemia in experimental rabbits by phenylhydrazine was optimized in terms of dose, dose interval and number of doses using response surface methodology. Central Composite Design was employed using five levels for each of the three input variables. Degree of hyperbilirubinemia was measured in terms of bilirubin level in serum of animals. A dose dependent significant elevation (P<0.05) of total serum bilirubin level was observed which was optimized by using eight factorial, six axial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The use of RSM to optimize fermentation conditions is mainly based on the following experiments [ 13 ]: 1) using the Plackett-Burman design to identify factors that significantly impact the fermentation process; 2) determining the path of steepest ascent to ascertain the approximate range of the best fermentation conditions using the key factors; and 3) performing the Box-Behnken test design to establish the fermentation model and determine the optimal fermentation conditions. RSM has been widely used to optimize microbial fermentation processes, and it can determine the impact of multiple factors [ 14 ]. Furthermore, RSM can be used to optimize fermentation conditions such that they meet the nutritional needs of a specific microorganism, thus avoiding the unnecessary addition of excess components in the culture medium [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of RSM to optimize fermentation conditions is mainly based on the following experiments [ 13 ]: 1) using the Plackett-Burman design to identify factors that significantly impact the fermentation process; 2) determining the path of steepest ascent to ascertain the approximate range of the best fermentation conditions using the key factors; and 3) performing the Box-Behnken test design to establish the fermentation model and determine the optimal fermentation conditions. RSM has been widely used to optimize microbial fermentation processes, and it can determine the impact of multiple factors [ 14 ]. Furthermore, RSM can be used to optimize fermentation conditions such that they meet the nutritional needs of a specific microorganism, thus avoiding the unnecessary addition of excess components in the culture medium [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…PHZ is a potent oxidizing agent that generates a wide array of PHZ-derived radicals such as phenyldiazene, phenylhydrazyl radical, and benzene-diazonium ions, and our study showed elevated serum MDA and NO levels in the PHZ-exposed rats ( Parvaz et al, 2022 ). Our findings showed that treating anemic rats with Ech significantly decreased MDA and NO levels which posssbily can be explained by scavenging active oxygen radicals ( Nawaz, Shad & Iqbal, 2016 ) or inhibiting lipid peroxidation ( Lebedev, Ivanova & Levitsky, 2008 ). As an antioxidant, Ech can bind to ROS deactivating them and protecting against oxidative stress and cellular damage.…”
Section: Discussionmentioning
confidence: 66%
“…exposure to chemicals, drugs, or virus infections induce acute liver injury ( Ramirez et al, 2018 ) Due ot its effect on elevating liver enzymes, PHZ has been proposed as to have a hepatotoxic effect on hepatocytes ( Obayuwana et al, 2022 ) Chronic liver disease result in normocytic and macrocytic anemias ( Allahmoradi, Alimohammadi & Cheraghi, 2020 ). PHZ induces jaundice through direct oxidation of Hb o generating oxyhemoglobin and methemoglobin, and RBC hemolysis increasing levels of unconjugated bilirubin ( Nawaz, Shad & Iqbal, 2016 ; Zhang et al, 2015 ). Levels of total bilirubin increase due to decreased uptake and conjugation by the dysfunctioning hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were divided equally into four groups as: A (untreated), B (negative control/anemic), C (positive control/IPS) and D (Fe(III)-rhamnoxylan). Iron-deficiency anemia was induced as reported earlier [ 45 ] by oral administration of 11 µg kg −1 per day phenylhydrazine for two days. The treatment was started after 4th day of the induction of anemia.…”
Section: Methodsmentioning
confidence: 99%